Innovative Approaches and Solutions in Advanced Intelligent Systems - Margenov, Svetozar; Angelova, Galia; Agre, Gennady; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This volume is a selected collection of papers presented and discussed at the International Conference "Advanced Computing for Innovation (AComIn 2015)". The Conference was held at 10th -11th of November, 2015 in Sofia, Bulgaria and was aimed at providing a forum for international scientific exchange between Central/Eastern Europe and the rest of the world on several fundamental topics of computational intelligence. The papers report innovative approaches and solutions in hot topics of computational intelligence - advanced computing, language and semantic technologies, signal and image processing, as well as optimization and intelligent control.
Advanced Computing -- Language Semantic And Content Technologies -- Signal And Image Processing -- Optimisation And Intelligent Control.
Keywords: Computational intelligence; Artificial intelligence; Computational Intelligence; Artificial Intelligence